Understanding Political Realism: A Review of the Thoughts of Thucydides, Machiavelli, Hobbes, and Morgenthau - Agung Wicaksono; Cifebrima Suyastri; Rio Sundari (Journal of Government and Political Issues, 2022)
This article discusses one of the basic concepts in political science and international relations, namely realism. As a perspective often used to analyze various political phenomena, it is essential to re-understand the concept of realism itself as a whole. This article attempts to provide a clear picture of what realism is meant and explain the history of realism from various realism thinkers. This article reviews the realism concept of 4 characters, namely Thucydides, Machiavelli, Hobbes, and Morgenthau. This article explains that each thinker has their arguments for explaining realism. Hopefully, this article can provide readers with a complete understanding of realism as a concept or perspective often used in political science.